2021
DOI: 10.55563/clinexprheumatol/xspect
|View full text |Cite
|
Sign up to set email alerts
|

The association between active proliferative lupus nephritis during pregnancy and small for gestational age newborns

Abstract: ObjectiveTo analyse maternal variables associated with occurrence of small for gestational age (SGA) newborns in pregnancies of women with systemic lupus erythematosus (SLE), considering clinical and laboratory characteristics prior to conception, during gestation and comorbidities. Methods Retrospective cohort study with SLE pregnant patients and singleton deliveries after 22 weeks. SGA newborn was defined as birth weight below 10 th percentile and SLE activity at conception and during gestation was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In many cases, these are attributed to growth problems during pregnancy. The background can be associated with many things, such as maternal smoking (regardless of SLE), high blood pressure, chronic kidney disease, antiphospholipid antibodies, disease-related characteristics and use of drugs [ 4 , 26 , 27 ]. Commonly, all these predisposing things can cause placental dysfunction by several different mechanisms such as inadequate perfusion, thrombosis or uncontrolled activation of complement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, these are attributed to growth problems during pregnancy. The background can be associated with many things, such as maternal smoking (regardless of SLE), high blood pressure, chronic kidney disease, antiphospholipid antibodies, disease-related characteristics and use of drugs [ 4 , 26 , 27 ]. Commonly, all these predisposing things can cause placental dysfunction by several different mechanisms such as inadequate perfusion, thrombosis or uncontrolled activation of complement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently shown that SLE patients with active LN during pregnancy experience significantly higher incidences of lupus flares, fetal loss, PE or eclampsia, preterm birth, and FGR. [ 24 , 25 ] While pulmonary arterial hypertension (PAH) is relatively rare in SLE patients, it is associated with a poor prognosis and high mortality rate during pregnancy. [ 26 ] A systematic review analyzed 13 studies including 272 pregnant women with PAH.…”
Section: Determination Of Pregnancy Timing In Sle Patientsmentioning
confidence: 99%